Proceedings of the Second International Conference on Internet-of-Things Design and Implementation 2017
DOI: 10.1145/3054977.3054999
|View full text |Cite
|
Sign up to set email alerts
|

Learning Execution Contexts from System Call Distribution for Anomaly Detection in Smart Embedded System

Abstract: Existing techniques used for intrusion detection do not fully utilize the intrinsic properties of embedded systems. In this paper, we propose a lightweight method for detecting anomalous executions using a distribution of system call frequencies. We use a cluster analysis to learn the legitimate execution contexts of embedded applications and then monitor them at run-time to capture abnormal executions. We also present an architectural framework with minor processor modifications to aid in this process. Our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 37 publications
(69 reference statements)
0
46
0
Order By: Relevance
“…• CPS platform. We assume the initial state (i.e., the training stage) of the application is trustworthy, which is a general requirement of most behavior-based intrusion detection systems [31]. We also assume the runtime monitoring module (running on the host) is trusted and cannot be disabled or modified.…”
Section: Attack Model and Assumptionsmentioning
confidence: 99%
“…• CPS platform. We assume the initial state (i.e., the training stage) of the application is trustworthy, which is a general requirement of most behavior-based intrusion detection systems [31]. We also assume the runtime monitoring module (running on the host) is trusted and cannot be disabled or modified.…”
Section: Attack Model and Assumptionsmentioning
confidence: 99%
“…Authors of [19] have an anomaly model built using system call frequency distribution and clustering techniques to detect when processes deviate from their standard profiles. Similar to the anomaly frameworks of [13], [14], the model of [19] has no temporal modeling of the events and can only be used for post-mortem analysis. Furthermore, the authors of [20] used the statistical metric of entropy to implement an anomaly detection model for network logs.…”
Section: Related Workmentioning
confidence: 99%
“…Otherwise, the adversary can perform more active attacks than what is described above -this is out of scope for this paper and we intend to analyze it in future work. There are various other threats faced by real-time systems [14], [26]- [29], [31] -most of these techniques are about intrusion detection and hence complementary to those presented here.…”
Section: A Adversary Modelmentioning
confidence: 99%
“…Hence, any perturbations to these operational modes can result in the safety of such systems being compromised. On one hand, recent studies [14], [26]- [29], [31] have shown that the security of real-time systems can be improved by taking advantage of these very properties, viz., predictability (or regularity) in their behavior. Such security mechanisms try to detect abnormal deviations from expected patterns.…”
Section: Introductionmentioning
confidence: 99%